Design, synthesis and anticancer activity studies of 3-(coumarin-3-yl)-acrolein derivatives: Evidenced by integrating network pharmacology and vitro assay - Chen, Lexian; Lv, Qianqian; Cai, Jianghong; Liang, Jiajie; Liang, Ziyan; Lin, Jiahui; Xiao, Ying; Chen, Ruiyao; Zhang, Zhiling; Hong, Yue; Ji, Hong (Frontiers in Pharmacology, 2023)
Coumarin derivatives have diverse structures and show various significant biological activities. Aiming to develop more potent coumarin derivatives for cancer treatment, a series of coumarin acrolein hybrids were designed and synthesized by using molecular hybridization approach, and investigated for their antiproliferative activity against A549, KB, Hela and MCF-7 cancer cells as well as HUVEC and LO2 human normal cells. The results indicated that most of the synthesized compounds displayed remarkable inhibitory activity towards cancer cells but low cytotoxicity on normal cells. Among all the compounds, 5d and 6e were the most promising compounds against different cancer cell lines, especially for A549 and KB cells. The preliminary action mechanism studies suggested that compound 6e, the representative compound, was capable of dose-dependently suppressing migration, invasion and inducing significant apoptosis. Furthermore, the combined results of network pharmacology and validation experiments revealed that compound 6e induced mitochondria dependent apoptosis via the PI3K/AKT mediated Bcl 2 signaling pathway. In summary, our study indicated compound 6e could inhibit cell proliferation, migration, invasion and promote cell apoptosis through inhibition of PI3K/AKT signaling pathway in human oral epidermoid carcinoma cells. These findings demonstrated the potential of 3-(coumarin-3-yl)-acrolein derivatives as novel anticancer chemotherapeutic candidates, providing ideas for further development of drugs for clinical use.